Evaluation of the Safety, Tolerability, Pharmacokinetics, and Food Effect of Danirixin Hydrobromide Tablets in Japanese Healthy Elderly Participants. Issue 8 (6th May 2019) - Iida, Takayuki; Matsuzawa, Yuki; Ogura, Hirofumi; Nagakubo, Takashi; Wakamatsu, Akira; Ambery, Claire; Miller, Bruce E.; Lazaar, Aili L.; Numachi, Yotaro
Abstract: Danirixin is a selective and reversible CXC chemokine receptor 2 antagonist that may be useful for the treatment of respiratory diseases such as chronic obstructive pulmonary disease. This study aimed to evaluate the safety, tolerability, and pharmacokinetics of danirixin after administration of single oral doses of 10, 50, and 100 mg danirixin hydrobromide (HBr) tablets in the fed state (high‐fat meal) (part 1) and to evaluate the food effect (low‐fat meal) on the pharmacokinetics of danirixin after administration of a single oral dose of 50 mg danirixin HBr tablets (part 2). A total of 34 Japanese healthy elderly male participants were enrolled; 18 participants were included in part 1, and 16 in part 2. The systemic exposure to danirixin (maximum blood concentration [Cmax ] and area under the concentration‐time curve [AUC0‐t ]) increased in an approximately dose‐proportional manner. The exposure to danirixin was lower in the fed state (low‐fat meal) than in the fasted state (a 56% and 35% decrease in Cmax and AUC0‐t, respectively). This first study of danirixin in Japanese healthy elderly participants showed a favorable safety profile with no drug‐related adverse events and no clinically significant concerns in clinical laboratory values, vital signs, ocular examination, or electrocardiograms.